Frailty prevalence and factors associated with the Frailty Phenotype and Frailty Index: Findings from the North West Adelaide Health Study. (4th October 2017) - Thompson, Mark Q; Theou, Olga; Yu, Solomon; Adams, Robert J; Tucker, Graeme R; Visvanathan, Renuka
Abstract : Objective: To determine the prevalence of frailty and associated factors in the North West Adelaide Health Study (2004–2006) using the Frailty Phenotype (FP) and Frailty Index (FI). Methods: Frailty was measured in 909 community‐dwelling participants aged ≥65 years using the FP and FI. Results: The FP classified 18% of participants as frail and the FI 48%. The measures were strongly correlated ( r = 0.76, P < 0.001) and had a kappa agreement of 0.38 for frailty classification, with 37% of participants classified as non‐frail by the FP being classified as frail by the FI. Being older, a current smoker, and having multimorbidity and polypharmacy were associated with higher frailty levels by both tools. Female, low income, obesity and living alone were associated with the FI. Conclusion: Frailty prevalence was higher when assessed using the FI. Socioeconomic factors and other health determinants contribute to higher frailty levels.